2013
DOI: 10.1093/jxb/ert213
|View full text |Cite
|
Sign up to set email alerts
|

Piriformospora indica antagonizes cyst nematode infection and development in Arabidopsis roots

Abstract: The beneficial endophytic fungus Piriformospora indica colonizes the roots of many plant species, including the model plant Arabidopsis thaliana. Its colonization promotes plant growth, development, and seed production as well as resistance to various biotic and abiotic stresses. In the present work, P. indica was tested as potential antagonist of the sedentary plant-parasitic nematode Heterodera schachtii. This biotrophic cyst-forming nematode induces severe host plant damage by changing the morphogenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 41 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…Previous studies of inoculation of Arabidopsis thaliana roots with P. indica in an in vitro petri plate assay, provide support for direct inhibition of nematodes by P. indica. Fungal culture filtrate, as well as application of P. indica cell wall extract, significantly decreased the motility, infectivity, development and reproduction of the beet cyst nematode (Heterodera schachtii) (Daneshkhah et al, 2013). In this study, we investigated the potential of this fungus to protect soybean from damaging effects of the SCN in a more realistic greenhouse pot study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of inoculation of Arabidopsis thaliana roots with P. indica in an in vitro petri plate assay, provide support for direct inhibition of nematodes by P. indica. Fungal culture filtrate, as well as application of P. indica cell wall extract, significantly decreased the motility, infectivity, development and reproduction of the beet cyst nematode (Heterodera schachtii) (Daneshkhah et al, 2013). In this study, we investigated the potential of this fungus to protect soybean from damaging effects of the SCN in a more realistic greenhouse pot study.…”
Section: Discussionmentioning
confidence: 99%
“…It also decreased disease symptoms of F. culmorum, Pseudocercosporella herpotrichoides, and B. graminis on wheat (Deshmukh and Kogel, 2007;Serfling et al, 2007). Recently, Daneshkhah et al (2013) reported that inoculation of P. indica onto Arabidopsis roots in vitro antagonized the infection and development of cyst nematodes. In this study, we tested the ability of P. indica amended to soil of soybean plants to decrease reproduction, as measured by egg density, of the SCN.…”
Section: Introductionmentioning
confidence: 94%
“…Fungal root endophytes are a phylogenetically diverse group primarily occurring within the Ascomycota, although some belong to the Basidiomycota. Piriformospora indica (phyllum Basidiomycota) and particular isolates within Trichoderma and Fusarium species (phylum Ascomycota) have been reported to enhance growth of various plant species and to induce resistance to pests like insects and nematodes (Daneshkhah et al 2013;Vu et al 2006). Some research has also revealed positive effects of dark septate endophytes (DSE) which comprise a group of asexual ascomycetes and are characterized by dark melanized septa on plant growth, yield and nutrient uptake (Andrade-Linares et al 2011;Jumpponen 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Daneshkhah et al (2013) reported that the cell wall extract and culture filtrate of this endophytic fungus antagonized the growth and development of cyst nematode Heterodera schachtii in A. thaliana. The antagonists were shown to affect nematode penetration and life cycle in the host plant.…”
Section: Fungal Endophyte and Biotic Stressmentioning
confidence: 99%